2008
DOI: 10.1128/jb.01863-07
|View full text |Cite
|
Sign up to set email alerts
|

ATP-Induced Shrinkage of DNA with MukB Protein and the MukBEF Complex of Escherichia coli

Abstract: Fluorescence microscopic observation of individual T4 DNA molecules revealed that the MukBEF complex (bacterial condensin) and its subunit, the MukB (a member of the SMC [structural maintenance of chromosomes] superfamily) homodimer, of Escherichia coli markedly shrunk large DNA molecules in the presence of hydrolyzable ATP. In contrast, in the presence of ADP or ATP-␥S, the conformation of DNA was almost not changed. This suggests that the ATPase activity of subunit MukB is essential for shrinking large DNA m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 24 publications
0
34
1
Order By: Relevance
“…Biochemical and structural studies have demonstrated that the binding of two ATPs is shared by the two head domains in the dimeric protein, bringing them together in a closed conformation (23). ATPase activity is stimulated by binding of the kleisin, MukF, and its associated protein, MukE (24), suggesting that the cycle of ATP binding and hydrolysis could regulate the opening and closing of the tripartite ring of the SMC complexes. This action has been invoked as a necessary part of the ability of the eukaryotic cohesin and condensin to trap DNA and allow it to exit (3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Biochemical and structural studies have demonstrated that the binding of two ATPs is shared by the two head domains in the dimeric protein, bringing them together in a closed conformation (23). ATPase activity is stimulated by binding of the kleisin, MukF, and its associated protein, MukE (24), suggesting that the cycle of ATP binding and hydrolysis could regulate the opening and closing of the tripartite ring of the SMC complexes. This action has been invoked as a necessary part of the ability of the eukaryotic cohesin and condensin to trap DNA and allow it to exit (3).…”
Section: Resultsmentioning
confidence: 99%
“…the ATPase activity of MukB is enhanced (24). Thus, we asked if the addition of MukEF to MukB-mediated catenation reactions that were inhibited by ATP led to a recovery of the catenation activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because full-length MukB affects the supercoiling and condensation of DNA (20,21,23,24), we also probed the ability of MukB-D, which lacks the DNA-binding head domain and much of the coiled coil (44) to stimulate Topo IV function. As with intact MukB, we observe that MukB-D is sufficient to stimulate the DNA decatenation and relaxation activities of Topo IV (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Both E. coli mukB − strains and smc − strains from Bacillus subtilis and Caulobacter crescentus show temperature-sensitive colony formation and an increase in the number of anucleate cells at the permissive temperature, suggesting a deficiency in chromosome segregation (5,7,(15)(16)(17)(18)(19). Moreover, a convincing array of experiments has demonstrated that MukB functions as a condensin in vitro and in vivo (20)(21)(22)(23)(24)(25)(26)(27)(28).…”
mentioning
confidence: 99%